2022
DOI: 10.1097/gme.0000000000002007
|View full text |Cite
|
Sign up to set email alerts
|

Prasterone in the treatment of mild to moderate urge incontinence: an observational study

Abstract: ObjectiveTo assess the effects of prasterone compared with hyaluronic acid on symptoms of mild to moderate urinary urgency in women with genitourinary syndrome of menopause.MethodsThis is an observational prospective cohort study. A total of 58 postmenopausal women were enrolled (from December 2019 to May 2021). Overactive Bladder Screener questionnaire, Patient Global Impression of Improvement questionnaire, International Consultation on Incontinence Questionnaire–Short Form, and International Quality of Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Their study suggested that 12 weeks of prasterone treatment may have a positive impact on the severity of urinary urge incontinence in women, although it should be noted that the study was conducted on a small group of patients. It is worth noting that 89.7% of women reported a reduction in the discomfort of urgency in the prasterone group compared to the hyaluronic acid group, as assessed by the Patient Global Impression of Improvement score ≤3 [75]. However, there is currently no available data on the effect of short-term local vaginal prasterone treatment for stress urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Their study suggested that 12 weeks of prasterone treatment may have a positive impact on the severity of urinary urge incontinence in women, although it should be noted that the study was conducted on a small group of patients. It is worth noting that 89.7% of women reported a reduction in the discomfort of urgency in the prasterone group compared to the hyaluronic acid group, as assessed by the Patient Global Impression of Improvement score ≤3 [75]. However, there is currently no available data on the effect of short-term local vaginal prasterone treatment for stress urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to positive effects on vulvovaginal atrophy (VVA) through the activation of vaginal androgen and estrogen receptors. Empirical evidence in this study suggests that intravaginal prasterone administration (dosage 6.5 mg) could be an effective treatment for postmenopausal women with genitourinary syndrome of menopause (GSM) affected by overactive bladder (OAB) 6,7 …”
Section: Introductionmentioning
confidence: 98%
“…Empirical evidence in this study suggests that intravaginal prasterone administration (dosage 6.5 mg) could be an effective treatment for postmenopausal women with genitourinary syndrome of menopause (GSM) affected by overactive bladder (OAB). 6,7 The aim of this study was to compare the efficacy of the transobturator tape (TOT) procedure combined with solifenacin (TOT-S) versus prasterone (TOT-P) in postmenopausal women affected by MUI with a predominant SUI component. A secondary endpoint was quality of life and sexual function evaluation.…”
mentioning
confidence: 99%